1999
DOI: 10.1046/j.1525-1381.1999.99130.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcomes of Cardiac Complications Following Elective Coronary Bypass Grafting

Abstract: Our objective was to determine the predictors of cardiac complications among a cohort of elective coronary artery bypass graft (CABG) surgery patients and to determine the relationship of such complications to subsequent quality of life and symptoms. A total of 248 patients were enrolled and 237 completed 6 month follow-up. The combined rate of both major and minor cardiac complications was 9.7% (n = 24). Patients in this study were evaluated preoperatively, monitored intraoperatively, followed immediately pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…[73][74][75] In contrast to evidence from animal experiments, several clinical studies have shown no benefit, and possibly even harm, from perioperative diuretic therapy in cardiac surgery patients: [76][77][78] • In a cohort of 248 coronary artery bypass graft (CABG) surgery patients, Charlson and colleagues found that preoperative diuretic therapy was an independent risk factor for postoperative complications. 79 • In a double-blind, randomized-controlled trial comparing infusions of furosemide, low-dose dopamine, or placebo from the start of surgery to 48 hours postoperative or intensive care unit discharge in 126 cardiac surgery patients, Lassnig and colleagues found no benefit of dopamine and a greater postoperative increase in serum creatinine in the group that received furosemide. These authors concluded that furosemide was detrimental to renal function after cardiac surgery.…”
Section: Diuretic Agentsmentioning
confidence: 99%
“…[73][74][75] In contrast to evidence from animal experiments, several clinical studies have shown no benefit, and possibly even harm, from perioperative diuretic therapy in cardiac surgery patients: [76][77][78] • In a cohort of 248 coronary artery bypass graft (CABG) surgery patients, Charlson and colleagues found that preoperative diuretic therapy was an independent risk factor for postoperative complications. 79 • In a double-blind, randomized-controlled trial comparing infusions of furosemide, low-dose dopamine, or placebo from the start of surgery to 48 hours postoperative or intensive care unit discharge in 126 cardiac surgery patients, Lassnig and colleagues found no benefit of dopamine and a greater postoperative increase in serum creatinine in the group that received furosemide. These authors concluded that furosemide was detrimental to renal function after cardiac surgery.…”
Section: Diuretic Agentsmentioning
confidence: 99%